DETERMINATION OF THE EFFICIENCY OF IMPLEMENTING BLOCKCHAIN TECHNOLOGY INTO THE LOGISTIC SYSTEM (Academia Science Repository, 2023)
The activity of enterprise is closely related to the need to transport goods. To date, the process of cargo delivery is complicated by: low speed of the logistics cycle; long document flow and the presence of errors in it; cargo safety. The need to improve the system of transport logistics of an industrial enterprise determines the relevance and objectivity of the research. The implementation of Blockchain technology will solve the existing problem in the field of supply management. In this study, the stages of implementation of blockchain technology are considered and the economic efficiency defined.